2018
DOI: 10.1111/anti.12407
|View full text |Cite
|
Sign up to set email alerts
|

Youth, Temporality, and Territorial Stigma: Finding Good in Camden, New Jersey

Abstract: The concept of “territorial stigmatisation” identifies the role of symbolic denigration in the production of marginalised places. In this paper, I draw on ethnographic research with a food justice organisation in Camden, New Jersey, to examine youth's responses to territorial stigma. The analysis demonstrates how Black and Latinx youth rewrite the story of Camden in a way that locates the “good” within it, using narratives of the city's prosperous history and possible futures to recuperate value within a stigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Moreover, in negotiating territorial stigma, the materiality of place was found to play an important role. Residents in the newly constructed housing projects mobilised the built environment to re‐inscribe place as an ordinary, suburban neighbourhood (Cairns ; Nayak ), functioning as an additional identity marker that served to distance them from negative cultural stereotypes. In this respect, the benefits of urban renewal are clearly unequally distributed: not only is stigma often used by governing actors to justify area‐based interventions, displacing social renters and attracting more affluent residents (De Koning ; Kipfer ; Tissot ; Tyler and Slater ), these new residents also disproportionally benefit from material improvements because it enables them to develop counter‐narratives against blemish of place.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in negotiating territorial stigma, the materiality of place was found to play an important role. Residents in the newly constructed housing projects mobilised the built environment to re‐inscribe place as an ordinary, suburban neighbourhood (Cairns ; Nayak ), functioning as an additional identity marker that served to distance them from negative cultural stereotypes. In this respect, the benefits of urban renewal are clearly unequally distributed: not only is stigma often used by governing actors to justify area‐based interventions, displacing social renters and attracting more affluent residents (De Koning ; Kipfer ; Tissot ; Tyler and Slater ), these new residents also disproportionally benefit from material improvements because it enables them to develop counter‐narratives against blemish of place.…”
Section: Resultsmentioning
confidence: 99%
“…Other scholars, however, question the degree to which territorial stigma is internalised by residents. Cairns (:1225) found that youths in Camden, New Jersey expressed “deep frustration with the singular, stigmatising narrative that so powerfully defined their city” and that has rendered them passive victims of their surroundings. While her respondents do not deny the challenges associated with living in Camden, they also describe such outsider accounts of present problems as “partial truths”.…”
Section: Resident Experiences Of Territorial Stigmamentioning
confidence: 99%
See 2 more Smart Citations
“…The Cleveland Hills, our coastline, our friendly and effacing people, our mighty River Tees and our wonderful history sum up Middlesbrough beautifully ... (Harry) These responses offer an alternative viewpoint on the town as a bleak postindustrial outpost, pointing instead to easy access to the countryside, recent urban regeneration, a vibrant nightlife and the immediacy of the coastline. As such, they seek to redraw the town and re-script place through an alternative grammar, largely derived from a local, "insider" perspective that doesn't negate that problems exist (Cairns 2018;Kirkness 2014). As one resident explained: "It's a lovely place to live", but "the steelworks closed.…”
Section: Location Live: Locating and Relocating Stigmamentioning
confidence: 99%